Reversal of the Symptoms of Diabetic Neuropathy through Correction of Vitamin D Deficiency in a Type 1 Diabetic Patient - David S. H. Bell (Case Reports in Endocrinology)
Vitamin D deficiency has been associated with both type 1 and type 2 diabetes as well as both the microvascular and macrovascular complications of diabetes. Vitamin D deficiency has been shown to be more common in diabetic patients who have symptoms of distal symmetrical polyneuropathy. In addition, vitamin D deficiency has been associated with a lower pain threshold which increases when vitamin D deficiency is corrected. Herein, I describe a type 1 diabetic patient with neuropathic symptoms so severe that he could not work and for which he needed narcotics for pain management and whose symptoms improved dramatically with correction of the vitamin D deficiency. To my knowledge, this is the first report of an improvement in severe symptoms of diabetic neuropathy with correction of vitamin D deficiency in a single patient.